Might female patients benefit more from bariatric surgery with respect to inflammation - Zhou, Qing; Yan, Pingping; Shi, Haiming; Yan, Ping (Frontiers in Surgery, 2022)
Background: Bariatric surgery is an effective method for severe obesity and its related comorbidities, in which inflammation plays a crucial role. Neutrophil-to-lymphocyte ratio (NLR) is a novel inflammatory marker and reflects systemic inflammatory response. The aim of this study was to investigate the changes of NLR and C-reactive protein (CRP) in patients undergoing laparoscopic sleeve gastrectomy (LSG) and to explore the related factors including gender. Methods: We retrospectively included 72 patients undergoing LSG in our hospital from 2017 to 2020. Clinical information, laboratory investigations as well as parameters derived from traditional and 2D strain echocardiography were collected. Univariate and Multivariate regression analysis were used to analyze the factors that correlated to NLR and CRP pre-surgery, and their changes post-surgery. Results: At baseline, all patients had normal left ventricular ejection fraction (LVEF). The myocardial performance index (MPI) (OR=1.218, p = 0.0142 ) and E/E’ (OR=1.311, p = 0.0014 ) were independently associated with CRP. LSG led to a significant decrease in inflammatory markers (NLR, 2.4±1.59 vs.1.7±0.86, P < 0.001; CRP, 5.6± 3.17 vs. 2.1±2.35mg/L, respectively, P < 0.001),which was more in female than male (NLR OR=2.81, P=0.03). Conclusions: The present study indicated a significant correlation between subclinical cardiac dysfunction and CRP among obese patients. Furthermore, female patients might benefit more from bariatric surgery on inflammation.